Improving Properties of Water-Based Drilling Mud using Hamburger Bean and African Oil Bean Shell Powders as Eco-friendly Fluid Loss Retardant Additive - Kayii, Joe Nwiyoronu; Onojake, Chukunedum Mudiagha; Oriji Garrick Onuoha; Obuzor, Gloria Ukalina (Journal of petroleum science and technology, 2024)
The processing of hamburger bean (HB) and African oil bean (AF) seeds for local consumption generates large amounts of waste (shells) that are considered an environmental nuisance. This manuscript presents the experimental result from the study on the utilization of HB and AF shell powders as fluid loss control additives in drilling mud. The mud filtration test was conducted at 25oC and 100 psi following with the American Petroleum Institute (API) guidelines for polymer-based mud. From the study, the HB-based mud sample showed a progressive decrease in the volume of fluid loss as the content of the HB additive increased. Furthermore, the fluid loss from mud samples with AF increased with an increase in its concentration, producing mud cake thickness between 2.2 and 2.8 mm. ultimately, the results demonstrate that HB is a cost-effective and sustainable green additive that can serve as a local alternative to the imported and expensive conventional filtrate control additives.